Impact of the Emerging Challenges on the Landscape of Digital Entrepreneurship - Majumdar, Swapan Kumar; Ghosh, Abhijit (International Journal of Management and Human Science (IJMHS), 2023)
This article scans the funding trends of the startups across the globe to unearth the emerging challenges, opportunities, and emerging digital technologies and analyzes the impact of the present economic downturn on the facilitators of digital entrepreneurship and how the leadership is igniting the creative passion of digital startups to transform the current geopolitical challenges into new opportunities. The scrutiny of digital entrepreneurs’ value creation processes and the innovation landscape of digital entrepreneurship reveals that the economic downturn and geopolitical conflicts have changed the opportunities basket of digital entrepreneurship. The emerging new digital technological tools are changing the means and processes of value creation. The political leadership and startup financiers are encouraging digital entrepreneurs to pursue more robust and disruptive innovations. The landscape of digital entrepreneurship is reconfiguring to handle the emerging challenges.